Meningkatkan Prestasi Belajar Akidah Akhlak melalui Metode Pembelajaran PAIKEM Tipe Jigsaw dan Index Card - Arief, Istijabah Sodik (STAI Auliaurrasyidin Tembilahan, 2021)
This study aimed to improve student's learning achievement of Akidah Akhlak using the jigsaw type and index card match. The research method used was classroom action research. The instruments were pretest and post-test, observation sheets, and interviews. The results of this study have reached the criteria that become the limiting indicators of success which are shown by increasing the category of aspects of learning achievement in each cycle. Likewise, with the results of the learning outcomes test, there was an increase in the average score, which in the first cycle was 66.4, in the second cycle was increased to 78.2 and there was an increase again to 88.6 and there were no more students who scored less than 75. The interviews have also responded positively to the learning process using this type of jigsaw and index card match. This research has shown that learning jigsaw type and index card match has had a positive impact on students in the learning process